1993
DOI: 10.1159/000243949
|View full text |Cite
|
Sign up to set email alerts
|

Breast Feeding and Formula Feeding Affect Differently Plasma Thyroid Hormone Concentrations in Infant Baboons

Abstract: We tested the hypothesis that plasma thyroid hormone levels in infant baboons are differentially affected by breast-feeding and nursery rearing. Infant baboons were breast-fed (n = 17), or fed formulas with a high polyunsaturated to saturated fat ratio (P/S) (n = 13), or a low P/S formula (n = 14). Plasma total triiodothyronine (T3) and free T3 (fT3) concentrations increased from 4 to 14 weeks of age in infants fed either formula, but decreased in breast-fed infants. At 9 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One possibility is altered thyroid hormone homeostasis. We observed differences in thyroid hormone levels in controlled studies with breast-and formula-fed baboons during both the pre-and postweaning periods (32,33). The promoter of the CYP7A1 gene has several binding sites for thyroid hormone receptors that mediate the significant effects of thyroid hormones on bile acid formation (34).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is altered thyroid hormone homeostasis. We observed differences in thyroid hormone levels in controlled studies with breast-and formula-fed baboons during both the pre-and postweaning periods (32,33). The promoter of the CYP7A1 gene has several binding sites for thyroid hormone receptors that mediate the significant effects of thyroid hormones on bile acid formation (34).…”
Section: Discussionmentioning
confidence: 99%
“…Lewis et al [21] showed that the plasma concentration of triiodothyronine, one of the thyroid hormones having more potent biological activity than thyroxin, was higher in formula fed than breast fed infant baboons. In the present study triiodothyronine levels in plasma were higher in mother-reared than in the formulafed groups, however, within the four formula groups a higher ratio of C:W was associated with higher plasma levels of triiodothyronine.…”
Section: Discussionmentioning
confidence: 99%
“…Also, monkey infants can be raised in primate nurseries where the amount and timing of iron in the diet can be precisely controlled through use of infant formulas. Infant monkeys have been used extensively as models for human infants to study absorption, growth and development with formulas of different nutritional content [11,13,35,51,58,41,42,43,33,40,54,57].…”
Section: Introductionmentioning
confidence: 99%